Toma The Traffic Light Man - Djordjevic Dragolјub (Sociološki pregled, 2020)
A sociological portrait of the Romani Toma the Traffic Light Man, a windshield wiper on one of the central intersections in the city of Niš. He is an interesting figure, a city guy, poor as a church mouse, very observant and picky, a bit of a buffoon, somewhat reluctant and apprehensive, protected by his guardians; he has a delineated area of operation, he has been skilful with his squeegee from his childhood, he does what he likes to do in order to survive, he earns a pretty penny, and he is the envy of many. He does not yearn for compassion, he is rarely stigmatized, he is not impudent or bad-tempered, he does not impose on people or protest, his profession is underestimated but not at all easy, he is not messy or slipshod, he does not like misers, he does not loiter around the traffic lights or smoke. Toma the Traffic Light Man is at the forefront of the squeegee men, he towers above regular cleaners that we meet daily in Serbian towns. He did not establish the profession known as the squeegee man – he is just the best specimen, the ideal type.